Makers and clusters: Knowledge leaks in open innovation networks - Jessica D. Giusti; Fernando G. Alberti; Federica Belfanti (Journal of Innovation & Knowledge (JIK), 2020)
This paper aims at investigating the role of makers in open innovation networks by focusing on whether and how knowledge leaks occur in open innovation networks with makers. In the last years, makers have been widely recognized as conducive to innovation and growth in different fields through a novel and open approach. However, little is known about the role played by makers and, more specifically, about the flow of unintended knowledge - i.e. knowledge leaks. Data have been collected by iteratively deploying a snowball sampling technique in an Italian high-tech cluster with a dense and heterogeneous ecosystem of makers. Data analysis relied on social network analysis method and techniques. Findings shed light on a totally unexplored phenomenon and suggest intriguing implications both for theory and practice on whether and how knowledge is exchanged in innovation networks and how knowledge leaks occur.
Keywords: O03; 650; Cluster; Knowledge leak; Maker Movement; Multiplexity; Open innovation; SNA